Mechanical Properties and Acoustic Emission Properties of Rocks with Different Transverse Scales - Xi Yan; Li Jun; Liu Gonghui; Guo Xueli (Shock and Vibration)
Since the stability of engineering rock masses has important practical significance to projects like mining, tunneling, and petroleum engineering, it is necessary to study mechanical properties and stability prediction methods for rocks, cementing materials that are composed of minerals in all shapes and sizes. Rocks will generate acoustic emission during damage failure processes, which is deemed as an effective means of monitoring the stability of coal rocks. In the meantime, actual mining and roadway surrounding rocks tend to have transverse effects; namely, the transverse scale is larger than the length scale. Therefore, it is important to explore mechanical properties and acoustic emission properties of rocks under transverse size effects. Considering the transverse scale effects of rocks, this paper employs the microparticle flow software PFC2D to explore the influence of different aspect ratios on damage mechanics and acoustic emission properties of rocks. The results show that (1) the transverse scale affects uniaxial compression strength of rocks. As the aspect ratio increases, uniaxial compression strength of rocks decreases initially and later increases, showing a V-shape structure and (2) although it affects the maximum hit rate and the strain range of acoustic emission, it has little influence on the period of occurrence. As the transverse scale increases, both damage degree and damage rate of rocks decrease initially and later increase.